FTA And Politeness Strategies In Prospective Studentsâ Personal Statements To Apply For A Masterâs Program Abroad - Iswara, Ratna Widya; Saleh, Mursid (English Education Journal, 2017)
Face threatening acts (FTAs) are sometimes unavoidable in communication. Thus, politeness strategies to soften the FTAs are needed to mitigate the risk of face loss. This study was aimed to investigate FTAs, politeness strategies and factors that influenced the choice of politeness strategies in prospective studentsâ personal statements to apply for a masterâs program abroad. This research applied descriptive qualitative method. In collecting the data, the writer used documentary method to gather 11 personal statements from prospective master students. The data were analyzed based on politeness theory proposed by Brown and Levinson (1987). The results showed that all eleven successful personal statements contained both face threatening acts and politeness strategies. The total face threatening acts found were 147 including the acts that threatened both the positive and negative face. Among all FTAs, boasting became the highest occurrence. From four strategies in doing FTAs, only positive politeness and negative politeness were used. The highest occurrence of positive politeness was being optimistic, and using hedge for negative politeness strategy. Power, distance, rank of imposition, type of FTA and gender became the factors that influenced the choice of politeness strategies.